Sorption behavior and mechanisms of thallium to microplastics - Liu, Min; Song, Xiaocheng; Wang, Qian; Li, Shilei; Kou, Siwang; Gao, Zhenhui; Zhuang, Wen (Frontiers in Marine Science, 2022)
Thallium (Tl) is a metal of high toxicity, and the problem of Tl pollution is being faced globally. However, environmental data on Tl are still scarce and its biogeochemical behaviors remain mostly unclear. Studies have revealed the potential transport of other heavy metal by microplastics (MPs), but there is no report on the interactions between Tl and MPs yet. Therefore, we studied the adsorption of Tl by the three most commonly detected MPs, i.e., polyethylene (PE), polystyrene (PS), and polypropylene (PP) in fresh and seawater. We considered the effects of particle size, pH and competitive cations on adsorption capacity. The results showed PS has the highest adsorption capacity for Tl which was mainly through surface complexation. PS showed the lowest crystallinity and had the most oxygen-containing functional groups among the studied MPs. The adsorption of Tl on PE and PP was dominated by physical adsorption. The adsorptions exhibited significant salinity and pH dependence. Dominant cations in seawater competed with Tl ions for adsorption sites on MPs. With the increase in pH, the deprotonation of the carboxyl functional groups on MPs was enhanced, which increased the effective adsorption sites and promoted the adsorption of Tl. However, the adsorption capacity of the studied MPs for Tl was much lower than the corresponding capacity of natural minerals (clay, iron and manganese oxides) previously reported. Therefore, MPs may not be the main factors affecting the environmental behavior of Tl. This study provides valuable information for the study of thallium’s environmental behavior and ecological risk assessment.